Nucleotide-induced conformational changes in the Escherichia coli NADH:ubiquinone oxidoreductase (complex I). (19th September 2008) - Pohl, Thomas; Schneider, Daniel; Hielscher, Ruth; Stolpe, Stefan; Dörner, Katerina; Kohlstädt, Markus; Böttcher, Bettina; Hellwig, Petra; Friedrich, Thorsten
Abstract : The energy-converting NADH:ubiquinone oxidoreductase, also known as respiratory complex I, couples the transfer of electrons from NADH to ubiquinone with the translocation of protons across the membrane. Electron microscopy revealed the two-part structure of the complex consisting of a peripheral and a membrane arm. The peripheral arm contains all known cofactors and the NADH-binding site, whereas the membrane arm has to be involved in proton translocation. Owing to this, a conformation-linked mechanism for redox-driven proton translocation is discussed. By means of electron microscopy, we show that both arms of the Escherichia coli complex I are widened after the addition of NADH but not of NADPH. NADH-induced conformational changes were also detected in solution: ATR-FTIR (attenuated total reflection Fourier-transform infrared) of the soluble NADH dehydrogenase fragment of the complex indicates protein re-arrangements induced by the addition of NADH. EPR spectroscopy of surface mutants of the complex containing a covalently bound spin label at distinct positions demonstrates NADH-dependent conformational changes in both arms of the complex.